The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s00414-009-0331-1
|View full text |Cite
|
Sign up to set email alerts
|

One person with two DNA profiles: a(nother) case of mosaicism or chimerism

Abstract: Nuclear DNA markers, such as short tandem repeats (STR), are widely used for crime investigation and paternity testing. STR were used to determine whether a piece of tissue regurgitated by a dog was part of the penis of a dead, emasculated, man. Unexpectedly, when analyzing the recovered material and a blood sample from the deceased, five out of the 18 loci differed. According to the results, one could have concluded that these samples originated from two different persons. However, taking into account context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…For instance, three or four alleles at a locus could be indicative of two or more contributors. Consequently, without knowing the circumstances surrounding the case, the subsequent interpretation will be conditioned only on the STR analysis assumptions and could lead to false conclusions [12]. Molecular studies of chimerism on different tissues should be considered in such cases because many mosaic cell lines could be found to be chimeric if adequately tested.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, three or four alleles at a locus could be indicative of two or more contributors. Consequently, without knowing the circumstances surrounding the case, the subsequent interpretation will be conditioned only on the STR analysis assumptions and could lead to false conclusions [12]. Molecular studies of chimerism on different tissues should be considered in such cases because many mosaic cell lines could be found to be chimeric if adequately tested.…”
Section: Discussionmentioning
confidence: 98%
“…DNA can be collected from any biological material, like for example, blood, semen, hair, bones, skin and saliva, being the same regardless of the cell types that are used. There are some rare exceptions, such as individuals called chimaeras (Castella et al, 2009).…”
Section: Dna In Forensicsmentioning
confidence: 99%
“…The examinations were 20% multiple choice (20 questions) and 80% short answer/essay (7–10 questions). The research papers were based upon case studies in the primary literature selected from various journals including those shown in Table and approved by the instructor in advance. The students selected a wide range of topics as reflected in the table.…”
Section: Evaluation and Testingmentioning
confidence: 99%